Peningkatan Kompetensi Guru BK Melalui Pengintegrasian STEAM Berbasis Neurosains - Susilo, Agus Tri; Purwaningrum, Ribut; Surur, Naharus; Asrowi, Asrowi; Kholili, Ma'rifatin Indah; Suryawati, Citra Tectona; Dewantoro, Adi (DEDIKASI: Community Service Reports, 2023)
The purpose of community service activities is to train guidance and counseling Teachers to integrateScience, Technology, Engineering, Art and Mathematics (STEAM) based on neuroscience in the implementation of guidance and counseling services in schools. The implementation of community service involves partners, namely counseling teachers in Boyolali Regency, a total of 50 people. The training activity was carried out 4 times the concept of the activity namely On Job Training 1, In Service Training 1, On Job Training 2 andIn Service Training 2 and equivalent to 40 Hours of Training. The data collection technique uses the Brammer & Shostrom evaluation instrument. Data analysis techniques using. Datapretest and posttest statistically analyzed using different tests (paired sample t-test). The result is the initial measurement (pretest) mastery of teacher competencies related to neuroscience-based STEAM by 48% while the final measurement (posttest) at 73%, so there is an increase in teacher competence due to training by 25%. These results show the commitment, hard work and desire to learn of the guidance and counseling teachers who are outstanding. Hope they can do it experiential learning in their respective schools so as to create many best practice which other guidance and counseling teachers can refer to.